CHEMICAL CASTRATION AGAINST PEOPLE SEXUAL VIOLENCE AGAINST CHILDREN - Hartanto (DE'RECHTSSTAAT, 2024)
Cases of sexual violence against children increase every year in Indonesia. Based on data from the Ministry of Women's Empowerment and Child Protection (Kempppa), the total number of children who were victims of sexual violence from 2019 to 2021 increased. From 2019 to 2020, cases of sexual violence against children increased to 6,980 cases, then from 2020 to 2021 there was another increase to 8,730 cases. This study aims to determine and analyze the imposition of prison sentences for perpetrators of sexual intercourse with children in Indonesia; about chemical castration for perpetrators of sexual violence against children in Indonesia; about children as victims of sexual violence against children. The research method used is normative juridical which is sourced from secondary data, the material legal analysis is qualitative. The results of the study found that the imposition of prison sentences for perpetrators of sexual intercourse with children is threatened with a minimum prison sentence of 5 (five) years to the death penalty (in certain cases), as well as how many additional chemical castration sentences meet the requirements as decisions that cannot be accepted by human reason. Sexual violence against children is a criminal act regulated in several Constitutions and other laws in Indonesia. The punishment of chemical castration is a decision that has become positive law, but several parties consider it inhumane, including the statement of Komnas HAM.